PENGARUH KEPEMILIKAN MANAJERIAL DAN KINERJA KEUANGAN TERHADAP KEBIJAKAN DEVIDEN - Adiaksa, Nanda; Novianti, Neva (Jurnal Kajian Akuntansi dan Auditing, 2024)
This research aims to test and prove managerial ownership and financial performance of dividend policy in banking companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The method used is a quantitative method processed with SPSS 26, the data source obtained is secondary data obtained from each company's website and the Indonesian Stock Exchange website. The sampling technique used in this research was the purposive sampling method, so that there were 12 samples that met the criteria. The techniques and data analysis used are descriptive statistics and multiple linear regression analysis. Based on the results of statistical tests, it was found that managerial ownership has no effect on dividend policy, because the number of shares owned by managers is relatively small. Meanwhile, financial performance influences dividend policy, because the higher the financial performance figure, the higher the company's activity level, so the dividend policy decreases.